Petrology and U-Pb zircon age of the Variscan porphyroclastic Rand Granite at the southeastern margin of the Central Schwarzwald Gneiss Complex (Germany) - Altherr, Rainer; Hanel, Michael; Schwarz, Winfried H. (International journal of earth sciences, 2019)
The Variscan Rand Granite as defined in this paper is a deformed I-type biotite granite that intruded along the southern-to-southeastern margin of the Central Schwarzwald Gneiss Complex. Former K-feldspar megacrysts (now porphyroclasts) of this K-Mg-rich alkali-calcic granite frequently show zonal crystallographic arrangement of mineral inclusions and are enclosed in a matrix of plagioclase, K-feldspar, quartz, biotite, apatite, zircon, and magnetite. Minor sphene and allanite are mostly altered. K-feldspar is orthoclase with perthitic exsolutions. Myrmekite is common and typically replaces marginal K-feldspar. Both feldspars show cataclastic and incipient ductile deformation that took place within the stability field of biotite (≥ 400 °C) as proven by grey varieties of Rand Granite with stable biotite. At most places, however, the Rand Granite shows a reddish colour, caused by late-stage chloritization of biotite and formation of hematite within K-feldspar. Furthermore, plagioclase became partially altered to sericite. This hydrothermal alteration took place at temperatures below the stability of biotite (< 400 °C). In situ ion probe U-Pb dating on zircon gave a concordant age of 330.9 ± 4.8 Ma (2σ), interpreted as the intrusion age of the Rand Granite. A large number of younger concordant to slightly discordant zircon ages between 309 and 90 Ma are interpreted to be due to episodic Pb loss during hydrothermal alteration. The Rand Granite apparently does not contain zircon domains older than the intrusion age and, furthermore, shows relatively high Zr contents (247-358 µg/g). These characteristics suggest high magma temperatures of at least 850-900 °C. The granitic magma most probably resulted from remelting of K-rich mafic to intermediate rocks in the middle crust at H2O-undersaturated conditions. Low Sr/Y ratios suggest a garnet-free residuum, which is only possible at pressures below ~ 0.9 GPa.